Factors Associated with Safe Sexual Behavior Among MSM Living with HIV: A Scoping Review - Theophylia Melisa Manumara; Kusman Ibrahim; Urip Rahayu (Eduvest - Journal of Universal Studies, 2024)
Background: Human Immunodeficiency Virus (HIV) is a virus that attacks lymphocytes, leading to a gradual decline in the body's immune system and increasing susceptibility to various diseases, including Acquired Immunodeficiency Syndrome (AIDS). Men who have sex with men (MSM) are at a higher risk of contracting HIV/AIDS due to unsafe sexual behavior. Objective: This scoping review aims to explore the factors associated with safe sexual behavior in MSM Living with HIV. Method: The scoping review is based on the framework by Arksey and O'Malley. A literature search involved various databases, such as EBSCO, PubMed, Science Direct, and CINAHL I, with the keywords: "Factors Associated" AND "Safe Sex Behavior" AND "Men Who Have Sex With Men OR MSM OR LSL". The selection process for research articles involved the use of inclusion criteria. The results were analyzed by extracting data into a data mapping table (PRISMA Flow Diagram). Results: 20 articles discussed factors related to safe sexual behavior among men with HIV/AIDS. These factors include individual perception, knowledge, and values. Discussion: It can be concluded that individual perception strongly influences safe sexual behavior among men, as individual perceptions can guide and motivate behavior.